SOSIALISASI DAN EDUKASI PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH DI TPA NOOR IMAN, SUNGAI BESAR, BANJARBARU SELATAN, KOTA BANJARBARU - Nurul Mardiati; Muhammad Reza Pahlevi; Atni Primanadini (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The coronavirus pandemic (COVID-19) has been declared a public health emergency or extraordinary event (KLB) and has spread to many countries and regions. The consequences of the COVID-19 pandemic are enormous and are felt by everyone around the world, including children who are growing and developing. In the Coronavirus Disease 2019 pandemic situation, which is abbreviated as COVID-19, every child without exception has the right to receive rights, protection, and clear information about the prevention and transmission of COVID-19.